ANTI-COMMUNISM AND SOCIAL CONTROL IN CHILE, THE EXPERIENCE OF THE COAL WORKERS IN LOTA AND CORONEL, BY THE MIDDLE OF THE XX TH CENTURY - Venegas Valdebenito, Hernán (Revista de Historia Social y de las Mentalidades, 2013)
In the early 1940’s coal region in Chile  was strongly influenced by the Communist  Party, a situation contradicted, according  to employers and national authorities, the  strategic nature of this industry in the whole  national economy. The paper examines  some political and business visions about  the problem and, moreover, describes  the mechanisms that tried to stop the  mobilization of workers and the communist  advance, severely straining social relations  in the area. Since then the workers’ demands  inevitably wore out, a phenomenon reinforced  further by the loss of relative importance of coal  in the Chilean economy.
Keywords: Mining; Coal; Cold War; Social Control; Anti-Communism